OPTIMIZING THE EXTRACTION CONDITIONS AND ANTIBACTERIAL ACTIVITIES OF SAPONIN FROM Celastrus hindsii Benth. - Trung Thanh, Pham; Thi Hong Van, Tran; Nhu Ngoc, Nguyen; Kim Dung, Vu (Journal of Forestry Science and Technology, 2020)
Saponins are natural compounds in plants which have been shown strong effects on health such as immune system stimulation, anti-cancer, analgesic, anti-vomiting, antioxidant, hypoglycemia, anti-fungal, bacteria and virus resistance. Celastrus hindsii Benth. is a medicinal plant species containing various bioactive compounds like flavonoids, saponins, tritrepenodid, diphenylpropanes, quinones that have been used as anticancer, anti-oxidant, antibacterial and anti-allergic drugs. The aim of this study is to optimize the extraction conditions of Saponin in Celastrus hindsii Benth. and identify its antibacterial activities. The results from experiments indicated that at the same conditions, the immersion method showed higher yeild of saponin content recovery (23.7 mg/g) than the ultrasound method (18.6 mg/g). Besides, the optimal parameters for the highest amount of saponins recovery by immersion method were also analyzed via surveying influenced factors and optimization by the Box-Behnken method. Accordingly, the optimal conditions for saponin extraction were identified: ethanol 74%, 3.32 hours, 80oC, the ratio of solvent per gram of material 1:16.5. The antibacterial activites of saponin extracted from Celastrus hindsii Benth. against some test bacteria like P. aeruginosa HS, S. areus VS1, E. coli CA were also recored with the strong resistance at high inhibition zones from 1.6 to 2.2 cm. Thus, saponin extracted from Celastrus hindsii Benth. in the above conditions can be used to produce protect and care products for human health.